Non-invasive endodontic treatment of large periapical lesions - Harry Huiz Peeters (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: In most cases of large periapical radiolucent lesions of pulpal origin, we often encounter a dilemmatic situation, such as whether to either treat these cases endodontically or surgically. Development of techniques, instruments and root medicaments as well as the tendency toward minimally invasive treatment, all support dentists to treat those cases using the minimal invasive principle (i.e. endodontically instead of surgically). Purpose: The purpose of this paper is to report and discuss the managing of periapical lesions by endodontic no invasive treatment. Case management: The patient with large periapical lesions were treated with noninvasive endodontic treatment. After 6 months, patients in this report were asymptomatic and radiolucencies had disappeared. When the root canal treatment is done according to accepted clinical principles and under aseptic condition, including cleaning, shaping, abturating as well as proper diagnosis, the healing process of the infected area will occur. Conclusion: Some lesions, however, may not be treated conservatively and may require surgical treatment for total elimination of the lesions.